Psychedelic targeting of metabotropic glutamate receptor 2 and its implications for the treatment of alcoholism - Domanegg, Kevin; Sommer, Wolfgang H.; Meinhardt, Marcus W. (Cells, 2023)
Alcohol abuse is a leading risk factor for the public health burden worldwide. Approved pharmacotherapies have demonstrated limited effectiveness over the last few decades in treating alcohol use disorders (AUD). New therapeutic approaches are therefore urgently needed. Historical and recent clinical trials using psychedelics in conjunction with psychotherapy demonstrated encouraging results in reducing heavy drinking in AUD patients, with psilocybin being the most promising candidate. While psychedelics are known to induce changes in gene expression and neuroplasticity, we still lack crucial information about how this specifically counteracts the alterations that occur in neuronal circuits throughout the course of addiction. This review synthesizes well-established knowledge from addiction research about pathophysiological mechanisms related to the metabotropic glutamate receptor 2 (mGlu2), with findings and theories on how mGlu2 connects to the major signaling pathways induced by psychedelics via serotonin 2A receptors (2AR). We provide literature evidence that mGlu2 and 2AR are able to regulate each other’s downstream signaling pathways, either through monovalent crosstalk or through the formation of a 2AR-mGlu2 heteromer, and highlight epigenetic mechanisms by which 2ARs can modulate mGlu2 expression. Lastly, we discuss how these pathways might be targeted therapeutically to restore mGlu2 function in AUD patients, thereby reducing the propensity to relapse.